Պետությունը որպես ազգի հիմնախնդրի լուծման գերխնդիր հնչակյանների քաղաքական հայեցակարգում - Aramazd Mkrtchyan (ՀՀ ԳԱԱ հրատ.)
The article brings about the Hnchak party’s approach toward the significant role of the state in the solution of national causes. The article deals with the history of Armenian political thought in late 19th and early 20th centuries. This is a very important period in our history taking into consideration the fact that during that period, persecutions against Armenian people by foreign invaders reached their culmination due to which the danger of physical extermination of Armenian people was obvious. Armenian people were deprived of any opportunity of political, economic and cultural developments and the issue of regaining the independence and statehood was of vital importance for Armenian people.
Keywords: Political Science